1965
DOI: 10.1111/j.1469-8137.1965.tb05394.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Physiology of Mycorrhizal Roots of Beech

Abstract: SUMMARYMycorrhizal roots of beech absorb [i'*C]glucose, fructose and sucrose at rates some two and a half times faster than uninfected roots. In the latter, sucrose is synthesized from all three sugars despite the presence of an active surface invertase, clearly suggesting that uptake from sucrose involves prior hydrolysis. There is only a small incorporation into polysaccharides by uninfected roots, this being into structural polymers. In contrast, mycorrhizal roots synthesize principally trehalose and glycog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…4 is possibly confirmed by the observations of Lewis and Harley (1965b) where [^'^CJsucrose was supplied to excised mycorrhizal roots under two conditions. In one group, the sheath and core remained intact during sucrose uptake and were then separated and analysed separately.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…4 is possibly confirmed by the observations of Lewis and Harley (1965b) where [^'^CJsucrose was supplied to excised mycorrhizal roots under two conditions. In one group, the sheath and core remained intact during sucrose uptake and were then separated and analysed separately.…”
Section: Discussionsupporting
confidence: 64%
“…In the studies of Lewis and Harley (1965b), uninfected roots tended to incorporate a lower proportion of sucrose supplied into 'insoluble' forms than did mycorrhizal roots. Interpretation of this fact is complicated by the synthesis of glycogen and protein by the fungus, and no direct evidence on the effect of mannitol on starch synthesis in uninfected beech roots is available.…”
Section: Discussionmentioning
confidence: 99%
“…Excised mycorrhizae of beech have been shown to convert glucose and fructose into the fungus specific metabolites trehalose and mannitol, respectively (LEWIS and HARLEY 1965;HARLEY and SMITH 1983;MARTIN et al 1985;MARTIN et al 1988). We are testing here if these activities can be used to develop a vitality test for ectomycorrhizae of Norway Spruce.…”
Section: Introductionmentioning
confidence: 95%
“…It is apparent that a close nutritional relationship exists between the two organisms. Mannitol is one of the carbohydrates used by bacteria, and Lewis and Harley (1965a, 1965b, 1965c showed that beech mycorrhiza secrete this substrate. Hassouma and Wareing (1964) found that in the presence of mannitol rhizosphere bacteria could fix nitrogen.…”
Section: Discussionmentioning
confidence: 99%